Rwanda : 2008 Article IV Consultation, Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criterion; Staff Report; Staff Supplement and Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for Rwanda's combined 2008 Article IV Consultation, Fifth Review Under the Three-Year Arrangement under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criterion is examined. Sound macroeconomic and structural policies backed by substantial donor assistance have led to macroeconomic stability, robust growth and low inflation, a comfortable level of international reserves, and significantly reduced external debt. Short-term risks to economic growth and the balance of payments have emerged because of the global financial crisis and economic slowdown.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet